Analytic representation of the distributional finite Hankel transform. (1985) - Singh, O. P.; Pathak, Ram S.
Abstract : Various representations of finite Hankel transforms of generalized functions are obtained. One of the representations is shown to be the limit of a certain family of regular generalized functions and this limit is interpreted as a process of truncation for the generalized functions (distributions). An inversion theorem for the gereralized finite Hankel transform is established (in the distributional sense) which gives a Fourier-Bessel series representation of generalized functions.